Praktik Panoptikon pada Liputan Narasi TV tentang Tragedi Kanjuruhan - Syafawi Ahmad Qadzafi (Kalijaga Journal of Communication, 2022)
This article shows the practice of panopticon in the Kanjuruhan Stadium tragedy through coverage of Narasi TV's “Brutal Moments Approaching Mass Death”. The deaths of 135 people at the Kanjuruhan Stadium in Malang during the match between Arema FC and Persebaya Surabaya drew various opinions and news points of view. Through data journalism that relies on open sources on the internet, Narasi TV gets 4,500 to 5,000 photos/videos from netizens as eyewitnesses. These data are used by Narasi TV to monitor and view the Kanjuruhan Tragedy in a comprehensive manner. The large amount of data shows that panopticon practices from spectators at the Kanjuruhan Stadium have occurred. This Narasi TV coverage evidences that the authorities such as security officers can now also be monitored through panopticon netizens with complete validation and verification from the mass media. If previously the panopticon was in the form of top-down, with the presence of panopticon netizens, monitoring practices are now more balanced. This article uses the method of cybermedia analysis and interviews with producers of coverage to see how Narasi TV produces and at the same time looks at the practice of panopticon in this coverage.